Tell Me Exactly What Happened : Dispatches from 911 - Burau, Caroline, 1973- (Book collections on Project MUSE., 2016)
"A veteran 911 operator shares her on-the-job experiences at both a single-person call center and a ground and air ambulance service. Whatever the position, the challenges for a dispatcher never end. Tragedy, boredom, and mind-bending weirdness are constant companions, as her stories--some funny, some odd, some sad--show. Regardless of the scenario, Caroline Burau handles each situation with efficiency, empathy, and humor"--